Empowering energy security through it: The path of export-oriented economies - Uktamov Khusniddin; Bauetdinov Majit; Sabirova Lola; Shoislamova Nargiza (E3S Web of Conferences)
The article explores the critical role of information technology (IT) in enhancing energy security for export-oriented economies. It addresses the growing demand for energy resources and the need for these economies to leverage technology to improve efficiency, sustainability, and competitiveness in the global market. Export-oriented economies often face vulnerabilities due to fluctuating energy prices, geopolitical tensions, and dependency on fossil fuels. The article emphasizes the importance of diversifying energy sources and implementing robust energy management systems.